Krisis Pendidikan di Palestina Tahun 2022 - Rohmatika, Idha Ismalia (Jurnal ICMES, 2023)
Education is a mean of empowerment for a nation, and the Palestinian nation is no exception. However, since the beginning of colonization in 1948 until today, Palestinian nation has experienced a crisis in education, and the main victims are children. One of the international organizations working to help children victims of conflicts and disasters worldwide is UNICEF (United Nations Children's Fund). In this article, the author analyzes the role of UNICEF in resolving the Palestinian education crisis using a postcolonialism approach, specifically Spivak's subaltern concept. The findings of this research are that UNICEF -as a party that voices subalterns- tends to bring their narratives and interests so that the programs they implement align with these interests. As a result, the educational crisis in Palestine continues to occur along with the ongoing occupation of the nation.